NILAI PRODUKSI RUMPUT GAJAH (Pennisetum purpureum Schumach & Thonn) DENGAN PEMUPUKAN ORGANIK DAN ANORGANIK SERTA INOKULASI MIKROORGANISME EFEKTIF (EM4) - Teguh Wibowo; Dwi Retno Lukiwati; Sumarsono Sumarsono (MEDIAGRO, 2017)
This study aimed to determine the equivalence of production value between the elephant grass (Pennisetum purpureum Scumach & Thonn) which was fertilized by an inorganic fertilizer (urea = P1) and the organic fertilizer (manure = P2 and bokashi = P3) were combined by inoculation an effective microorganisms EM4 = E. The study used the experimental design of split-plot on the basis of a randomized complete design consisting 3 replications. The main plot was 8 treatment combinations while the subplot was 3 defoliation periods (1, 2 and 3). Eight treatment combinations were: E0P0 (no EM4, no fertilizers); E1P0 (EM4, no fertilizers); E0P1 (no EM4, urea); E1P1 (EM4, urea); E0P2 (no EM4, manure); E1P2 (EM4, manure); E0P3 (no EM4, bokashi); and E1P3 (EM4, bokashi). The interaction effect fertilization and defoliation treatments was significant (P < 0.05) on the grass height, fresh forage production and nitrogen (N) production. This interaction effect was not significant (P > 0.05) on the number of tillers, dry matter (DM) production, digestibility of organic matter (OM) and digestibility of DM over the defoliation periods but the main effect in the form of defoliation periods was significant (P < 0.05) to the number of tillers and DM production. Number of tillers increased significantly (P < 0.05) throughout the defoliation periods whereas DM production increased significantly (P < 0.05) from the 1st defoliation to the 2nd defoliation and then decreased significantly (P < 0.05) in the 3rd defoliation. Fertilization of elephant grass used manure or bokashi which was inoculated by EM4 able to produce the number of tillers, grass height, fresh forage production and DM production which were equivalent of elephant grass which was fertilized by urea (without inoculation of EM4) but the N production was lower. This fertilization was only able to produce the number of tillers and DM production which were equivalent of elephant grass which was fertilized by urea (with inoculation of EM4) but grass height, fresh forage production and the N production were lower. Fertilization of elephant grass used manure, bokashi or urea (with or without inoculation of EM4) did not affect the elephant grass digestibility of DM and OM. Keywords: Bokashi,defoliation of elephant grass, elephant grass, EM4, manure,  urea.